GPETAFLR, a novel bioactive peptide from Lupinus angustifolius L. protein hydrolysate, reduces osteoclastogenesis. (August 2018) - Millan-Linares, M. Carmen; Lemus-Conejo, Ana; Yust, M. Mar; Pedroche, Justo; Carrillo-Vico, Antonio; Millan, Francisco; Montserrat-de la Paz, Sergio
Graphical abstract: Highlights: GPETAFLR reduced TRAP activity and the expression of osteoclast marker genes. GPETAFLR increased the release of anti-osteoclastogenic cytokines (IL-4 and IL-10). Lupinus angustifolius L. may prevent osteoclast-related diseases. Abstract: The effect of GPETAFLR, a peptide isolated from Lupinus angustifolius L. protein hydrolysate (LPH), on osteoclastogenesis was investigated. Human osteoclasts generated from monocytes were used to analyse the effects of GPETAFLR (50–100 µg/mL) on osteoclastogenesis using TRAP reaction, RT-qPCR, and ELISA procedures. LPS enhanced TRAP activity and the expression of osteoclast marker genes (TRAP, OSCAR, RANK, and CATHK) while downregulated the expression of OPG gene in human monocyte-derived osteoclasts. These effects were reduced with GPETAFLR. Moreover, LPS increased the release of osteoclastogenic cytokines (TNF-α, IL-1β, and IL-6) meanwhile GPETAFLR increased the release of anti-osteoclastogenic cytokines (IL-4 and IL-10) in the medium of human monocyte-derived osteoclasts. For the first time, we show that plant peptides from lupine protein hydrolysates have anti-osteoclastogenic activity. These exciting findings open opportunities for developing nutritional strategies with Lupinus angustifolius L. as dietary source of plant proteins, notably GPETAFLR, to prevent development and progression of osteoclast-related diseases.